Solitary Kaposi's sarcoma in retromolar region of an HIV positive patient: case report Sarcoma de Kaposi em região retromolar de um paciente HIV positivo: relato de caso - Maiara de Moraes; Marcelo Gadelha Vasconcelos; Rodrigo Gadelha Vasconcelos; Rafael Cabral; Igor Lira Gomes; Lélia Maria Guedes de Queiroz (Sociedade Brasileira de Patologia Clínica, 2012)
Kaposi's sarcoma is a malignant neoplasm of vascular origin. It occurs mainly among immune deficient individuals, thus it is the most common neoplasm among HIV- positive patients. Its pathogenesis is complex and has not been fully clarified. This case arouses particular interest due to its anatomic location in the retromolar region of a 39-year-old male HIV- positive patient, who presented low white blood cell count and was not undergoing antiretroviral therapy. The emergence of this lesion may be associated with highly active antiretroviral therapy (HAART) discontinuation and leukopenia. Hence, the reestablishment of therapy allows a suitable therapeutic approach and contributes to prognosis and survival rates. Sarcoma de Kaposi é uma neoplasia maligna de origem vascular que ocorre principalmente em indivíduos com deficiência imunológica, sendo a neoplasia mais comum em pacientes HIV positivos. Sua patogênese é complexa e não está bem estabelecida. Este caso é de interesse pela localização anatômica em região retromolar de paciente soropositivo, que apresentou baixa contagem de células brancas do sangue e que não realizava terapia antirretroviral. O surgimento da lesão pode estar associado à interrupção da terapia antirretroviral altamente ativa (HAART) e à baixa contagem leucocitária. Assim, o restabelecimento da terapia pode permitir a abordagem terapêutica e contribuir para o prognóstico e a sobrevida.